Morphological, immunohistochemical and ultrastructural characterization of the skin of turbot (Psetta maxima L.) - Failde, L.D. (2014)
This study was undertaken to identify the normal morphologic, immunohistochemical and ultrastructural features of skin of the turbot (Psetta maxima L.). In the turbot skin, three morphologically distinct layers were identified: epidermis, dermis and hypodermis. The epidermis was non-keratinizing, stratified squamous epithelium that varies in thickness from 5 to 14 cells and 60 to 100 μm in size. Goblet cells were seen randomly distributed between malpighian cells in the epidermal layer. These mucous cells were mainly located in the upper third of the epidermis and displayed a spherical to elongated morphology. Dermis was divided in two well-differentiated layers, the superficial stratum laxum and the deeper stratum compactum. Hypodermis was a loose layer mainly composed by adipocytes but we could observe variable amounts of fibroblast, collagen and blood vessels. In turbot two pigmentary layers could be identified: the pigmentary layer of dermis was located between basement membrane and dermis and the pigmentary layer of hypodermis immediately above the muscular layer. Three different types of chromatophores were present: melanophores, iridophores and xanthophores. The main differences observed between groups of fish with different colouration were in the amount of melanophores and xanthophores. The purpose of this article is to provide an overview of normal cutaneous biology prior to consideration of specific cutaneous alterations and diseases in turbot.